Building Digital Governance Capacity: Civil Service Development Strategies in the Era of Industry 4.0 - I Putu Gde Bayu Indra Wahyudi; Juwita Pratiwi Lukman (Universitas Pattimura, 2026)
Digital transformation driven by the Industry 4.0 paradigm requires governments not only to adopt information technologies but also to strengthen bureaucratic capacity to sustain digital governance practices. This study examines strategies for developing the capacity of civil servants in supporting digital governance at the local government level. The research was conducted at the Regional Civil Service and Human Resource Development Agency of Badung Regency using a qualitative approach with a descriptive–analytical design. Data were collected through field observations, in-depth interviews with human resource managers and civil servants, and analysis of institutional documents related to competency development programs. The data were analyzed using thematic analysis to identify key challenges and institutional strategies in bureaucratic capacity development. The findings reveal several structural constraints affecting digital governance capacity, including gaps in digital competencies among civil servants, limited motivation for professional development, and restricted budget allocations for continuous training programs. To address these challenges, the institution has implemented several capacity-building initiatives, such as digital competency–based training programs, the strengthening of adaptive bureaucratic work culture, and digital transformation awareness programs across government agencies. This study contributes to the governance literature by integrating bureaucratic capacity development with the digital governance framework, highlighting the role of civil servants as institutional actors in local digital transformation. The findings suggest that successful digital governance depends not only on technological infrastructure but also on the institutional capacity and professional development of the public bureaucracy.